2019
DOI: 10.1521/pedi_2018_32_350
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition and Social-Cognitive Correlates of Narcissistic Features

Abstract: Narcissistic personality disorder (NPD) is associated with both seeming indifference and hypersensitivity to social feedback. This study evaluated whether rejection sensitivity and empathic difficulties in NPD are accounted for by altered facial emotion recognition (FER). Two-hundred non-clinical individuals self-reported NPD features, rejection sensitivity, and empathy and performed an FER task assessing the ability to determine the presence or absence of an emotion when viewing neutral and negative facial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…For instance, the nodes of 'hypersensitivity', 'insecurity' and 'affective instability' reflect dimensions covered in the Hypersensitive Narcissism Scale [51] and neuroticism within the Five Factor Narcissism Inventory [52]. These aspects of narcissism have also been documented within published literature [12,27,53,54].…”
Section: Vulnerable Narcissismmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, the nodes of 'hypersensitivity', 'insecurity' and 'affective instability' reflect dimensions covered in the Hypersensitive Narcissism Scale [51] and neuroticism within the Five Factor Narcissism Inventory [52]. These aspects of narcissism have also been documented within published literature [12,27,53,54].…”
Section: Vulnerable Narcissismmentioning
confidence: 96%
“…Recognising the vulnerable dimension of narcissism has significant implications for treatment [7], including providing an accurate diagnosis and implementing appropriate technical interventions within treatment settings. Vulnerable narcissism, in marked contrast to the overt grandiose features listed in DSM-5 criteria, includes instances of depressed mood, insecurity, hypersensitivity, shame and identification with victimhood [8][9][10][11][12]. Pincus, Ansell [13] developed the Pathological Narcissism Inventory (PNI) to capture this narcissistic vulnerability in three factors.…”
Section: Introductionmentioning
confidence: 99%
“…Student studies reported more evidence of deficits in emotion recognition from facial expressions (e.g. Konrath et al, 2014;Martins et al, 2019;Wai & Tiliopoulos, 2012) whereas there were no such deficits reported in 4 studies from the broader population (Fan et al, 2010;Hengartner et al, 2014;Pajevic et al, 2018) and possibly enhanced recognition of subtle expressions (De Panfilis et al, 2019).…”
Section: Sample Populationmentioning
confidence: 91%
“…, Porter et al, 2014, exploitativeness (Hepper, Hart, Meek, et al, 2014), and fantasies of unlimited success and envy in a clinical sample (Bilotta et al, 2018). Those studies including measures of VN found that participants scoring highly were less confident about their social cognitive skills, rating empathy and emotional intelligence lower (Austin et al, 2014;Casale et al, 2019;Lannin et al, 2014;Lowicki & Zajenkowski, 2017;Zajenkowski et al 2018) despite appearing more emotionally reactive (De Panfilis et al, 2019;Jonason & Kroll, 2015;Rogoza et al, 2018;Wiehe, 2003;Zondag, 2007). In addition to PD, fantasy scores were also higher in VN when this scale was included (Given-Wilson et al, 2011;Jonason & Kroll, 2015).…”
Section: Measures Of Narcissismmentioning
confidence: 99%
“…Studies vary with regard to sensitivity and reactivity, but point towards a hyper-reactivity but not necessarily an accompanying interpersonal responsiveness in NPD. One study of facial emotion recognition confirmed that subjects with high NPD traits showed increased sensitivity for subtle cues of non-acceptance in negative or neutral facial expressions, which contributed to their intense angry feelings and accompanying self-focus (De Panfilis et al, 2019). This can further explain the often-contradictory presentations of narcissistic individuals as either or both hyper-vigilant and reactive or insensitive and dismissive.…”
Section: Internal Processingmentioning
confidence: 98%